JAK2 mutation, a potential cause of increasing Hemoglobin levels in symptomatic aged women - Zeinab Siahmargoie; Mohammad Taher Hojjati; Hadi Bazzazi; Khodaberdi Kalavi; Mana Zakeri; Hadi Joshaghani (Medical Laboratory Journal)
Background: Polycythemia Vera (PV) is a myeloproliferative neoplasm (MPN) characterized by the overactivity of erythroid progenitors, leading to excessive red blood cell (RBC) production. More than 90% of PV cases harbor a Janus kinase 2 (JAK2) gene mutation. This study aimed to assess the prevalence of JAK2 mutations in individuals with elevated hemoglobin (Hb) levels referred to the laboratory by physicians. Methods: In this descriptive cross-sectional study, genomic DNA from 72 patients was analyzed for JAK2 mutations using a TaqMan-specific probe. Results: Of the 72 patients, 24 (33.3%) were women and 48 (66.6%) were men. JAK2 mutations were detected in 33 cases (45.5%), while 39 (54.2%) were negative. Notably, 15 of 24 female patients (62.5%) tested positive for the JAK2 mutation, compared to 18 of 48 male patients (37.5%). Conclusion: Our findings suggest that screening for JAK2 mutations is particularly important in women with above-normal Hb levels.